Respuesta :
To invert this function, let's solve the expression for x. We start with
[tex] f(x) = y = 2^x+6 [/tex]
If we subtract 6 from both sides, we have
[tex] y-6 = 2^x [/tex]
Now we need to manipulate both sides so that the right hand side will consist only of x. To do so, we must perform the inverse function of [tex] 2^x [/tex].
[tex] 2^x [/tex] is an exponential function, because the variable is at the exponent (note the difference, with, for example, [tex] x^2 [/tex], where the exponent is always 2). The inverse function of an exponential function is the logarithm, taken with the same base as the exponential function.
So, the inverse function of [tex] f(x) = 2^x [/tex] is [tex] f^{-1}(x) = log_2(x) [/tex]. Let's apply this function to both sides to get
[tex] log_2(y-6) = x [/tex]
Which means that we can rename the variables and state that the inverse function is
[tex] f^{-1}(x) = log_2(x-6) [/tex]
i.e. option D.)
What is the inverse of the function below?
f(x) = 2^x + 6
1) Replace "f(x)" with "y" y = 2^x + 6
2) Interchange x and y: x=2^y + 6
3) Solve this for y: 2^y = x - 6 Take the log to the base 2 of both sides:
y = (log to the base 2 of) (x-6)
4) replace y with
-1
f (x)
We obtain:
-1
f (x) = (log to the base 2 of) (x-6)